Exploring Transportation Accessibility to Health Care among Vermont's Rural Seniors. Issue 1 (January 2015) - Battista, Geoffrey A.; Lee, Brian H. Y.; Kolodinsky, Jane; Heiss, Sarah N.
The aging baby boomer generation will have a profound impact on the demand for health care services in the United States. This impact will be felt strongly in rural areas, where the population in general is older and the supplies of health care services and alternative transportation are limited. This study employed a mixed-method approach to assess health care accessibility among seniors in the state of Vermont. A geographic information system was used to project health care accessibility according to the spatial characteristics of the health care and transportation systems. Subsequently, the mechanisms that shaped accessibility were assessed through semistructured interviews with 20 seniors and caregivers. The study found that health care accessibility varied among seniors, given the local health care supply, transportation, and individual resources at their disposal. Health care accessibility also was shaped by less tangible factors, which included social connectedness and personal preferences for care and transportation. The results suggested that mixed methods provided a more nuanced and valid perspective on health care accessibility. This perspective can better inform policy makers as they strive to accommodate rural senior preferences to age in place in a healthy manner.